OVIPOSITION PREFERENCE OF ð˜—ð˜ð˜¶ð˜µð˜¦ð˜ð˜ð˜¢ ð˜¹ð˜ºð˜ð˜°ð˜´ð˜µð˜¦ð˜ð˜ð˜¢ (Lepidoptera: Plutelidae) AND PARASITISM BY ð˜›ð˜³ð˜ªð˜¤ð˜©ð˜°ð˜¨ð˜³ð˜¢ð˜®ð˜®ð˜¢ ð˜±ð˜³ð˜¦ð˜µð˜ªð˜°ð˜´ð˜¶ð˜® (Hymenoptera: Trichogrammatidae) IN COLLARD GREEN - Massarolli, AngÃ©lica; Santos, Bruno da Silva; de Souza, Raquel Anjos; Butnariu, Alessandra Regina; Pereira, MÃ´nica Josene Barbosa; Moura, Mauricio Osvaldo; Foerster, LuÃs Amilton (REVISTA DE AGRICULTURA, 2021)
The damage caused by the diamondback moth is a limiting factor in the production of brassicaceous plants worldwide and biological control by an egg parasitoid may be an effective way to control this pest. Thus, understanding oviposition preferences of pests and parasitoids in crop plants can be a key factor in optimizing biological control programs. The present study was aimed at determining the oviposition preference of Plutella xylostella and Trichogramma pretiosum in collard greens. Bioassays consisted of collard plants in cages and P. xylostella adults released inside to lay eggs on the leaves. After 24 hours, the adults were removed and T. pretiosum females released. In another experiment, cardboard strips containing P. xylostella eggs were offered to T. pretiosum released in cages with a collard greens plant inside and replaced every 2 hours for 24 hours. The results showed that P. xylostella has a preference for laying eggs on the leaves of the middle region of the plant, on the upper part of the adaxial surface. For T. pretiosum, no preference was observed, but mean parasitism rates were highest on the upper region of the adaxial surface, where most of the eggs were found. In the second experiment, the highest mean parasitism rates by T. pretiosum were observed at temperatures ranging from 25.9 to 37.4 Â°C and relative humidity between 42 and 78% in the photophase. No parasitism occurred in scotophase, indicating that field releases should be performed preferably in the early hours of the morning.